CSR disclosure on the web: major themes in the banking sector. Issue 3 (2nd March 2015) - Vilar, Vítor Hugo; Simão, João
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Corporate social responsibility became a core topic in the management and activity of banks. Being a bidirectional, permanent, updateable and universal access communication channel, the internet contributed to transform the way the organizations report social responsibility to stakeholders. The purpose of this paper is to understand how the banks use their web sites to disclose their social responsibility concerns and activities. Design/methodology/approach – The globe was divided in 11 regions, according to geographic and cultural criteria. Information was gathered from the corporate web sites of the ten major banks in each region, and their contents were analyzed. Geographic patterns and the correlation to universal development indicators were studied. Findings – The banks disclose on their web sites information on environmental management and socioeconomic programs. Other recurrent themes are the support to education, fight against corruption, workers' welfare, corporate ethics and the existence of codes of conduct. There are geographic patterns in the quantity and detail of the information provided, as well as in the themes mentioned. The banks located in Europe, the American continent, and Oceania, are those who disclose more information. This confirms that the disclosure of social responsibility by the banks is larger and more detailed according to the development indexes of the country where they operate. Originality/value – The work studies the disclosure on the internet of information on social responsibility by the banks, being the first work to do it at the world level. This way, it provides a significant contribution to identify the themes that are more often disclosed and to establish comparisons between geographic areas.